Correlating the surface basicity of metal oxides with photocatalytic hydroxylation of boronic acids to alcohols - Leow, Wan Ru (2020)
Photoredox catalysis provides opportunities in harnessing clean and green resources such as sunlight and O2 , while the acid and base surface sites of metal oxides are critical for industrial catalysis such as oil cracking. The contribution of metal oxide surfaces towards photocatalytic aerobic reactions was elucidated, as demonstrated through the hydroxylation of boronic acids to alcohols. The strength and proximity of the surface base sites appeared to be two key factors in driving the reaction; basic and amphoteric oxides such as MgO, TiO2 , ZnO, and Al2 O3 enabled high alcohol yields, while acidic oxides such as SiO2 and B2 O3 gave only low yields. The reaction is tunable to different irradiation sources by merely selecting photosensitizers of compatible excitation wavelengths. Such surface complexation mechanisms between reactants and earth abundant materials can be effectively utilized to achieve a wider range of photoredox reactions.